THE AREA OF OCCURRENCE OF THE KEY PROBLEMS OF THE COMMERCIALIZATION OF INNOVATIONS - Valentina Parakhina; Ekaterina Novikova (Вестник Северо-Кавказского федерального университета)
The article describes the emergence ofthefield ofthe key problems ofcommercialization ofinnovations identified the most complex and labor-intensive, and are determined by their levels of solvability of infrastructure elements.